2022
DOI: 10.1002/wnan.1833
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity testing of nanomaterials

Abstract: Nanomaterials have outstanding and unprecedented advantageous material properties but may also cause adverse effects in humans upon exposure. Testing nanomaterials for genotoxic properties is challenging because traditional testing methods were designed for small, soluble molecules and may not be easily applicable without modifications. This review critically examines available genotoxicity tests for use with nanomaterials, including DNA damage tests such as the comet assay, gene mutation tests such as the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 245 publications
0
1
0
Order By: Relevance
“…No significant changes in white blood cell viability were found by Ballesteros et al after 24, 48, and 72 h of exposure to PS-NPs (PP-008-10) [23]. Moreover, in a different study, it was shown that despite the PS-NPs' size (29,44, or 72 nm), concentrations up to 100 µg/mL were not cytotoxic to the human peripheral blood lymphocytes [24]. Similarly, such tendency was observed in leukocytic cell lines: Raji-B, TK6, and THP-1 treated with PS-NPs (PP-008-10) [19].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…No significant changes in white blood cell viability were found by Ballesteros et al after 24, 48, and 72 h of exposure to PS-NPs (PP-008-10) [23]. Moreover, in a different study, it was shown that despite the PS-NPs' size (29,44, or 72 nm), concentrations up to 100 µg/mL were not cytotoxic to the human peripheral blood lymphocytes [24]. Similarly, such tendency was observed in leukocytic cell lines: Raji-B, TK6, and THP-1 treated with PS-NPs (PP-008-10) [19].…”
Section: Discussionmentioning
confidence: 85%
“…Given that DNA damage detected by the comet assay could be repaired before it results in a mutation, additional genotoxicity biomarkers, such as induction of micronuclei, must be included [ 44 ]. In our study, all PS-NPs concentrations induced a statistically significant increase of MN, yet no direct relationship between these two markers was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of benchmark genotoxic substances on cell viability. As a prerequisite to genotoxicity assessment, the 13 test substances were first tested for their cytotoxicity since genotoxicity should not be assessed at concentrations that highly affect their viability [13]…”
Section: Resultsmentioning
confidence: 99%
“…Regarding NBMs that did not affect cell viability, we chose to test them at 10, 25 and 50 μg/mL. These concentration were chosen so as to avoid assay interference of the NBMs [13,58] and in order to test the genotoxicity of most of the NBMs at comparable concentration, given their distinct impact on cell viability. X-ray irradiations were performed on a CIX2 irradiator (X Strahl Life Sciences, United Kingdom) performing at 250 kV.…”
Section: Cell Culture and Exposurementioning
confidence: 99%
See 1 more Smart Citation